Factors affecting the distribution and abundance of orchids in grasslands and herbaceous wetlands. Issue 4 (3rd July 2016) - Djordjević, Vladan; Tsiftsis, Spyros; Lakušić, Dmitar; Jovanović, Slobodan; Stevanović, Vladimir
Abstract : Grasslands, wet meadows, fens, bogs, and marshes represent important ecosystems that host many orchid species. However, research on the joint effect of the multi-scalar abiotic drivers on orchid distribution and abundance in these habitats is limited. In this study, we investigated factors associated with the occurrence and abundance of 42 orchid taxa in grasslands and herbaceous wetlands of 29 mountains and the surrounding low altitude areas in western Serbia (eastern Dinaric Alps, southeastern Europe). Niche analysis of orchids was performed using outlying mean index analysis (OMI). In addition, we used similarity profile analysis (SIMPROF) to classify orchid taxa into ecological groups, multi response permutation procedure (MRPP) to analyse the differences in orchid composition between vegetation types, and indicator species analysis (ISA) to detect orchids with an affinity to a certain type of vegetation and geological bedrock. The most important gradients that separate orchids within the sampled environmental conditions were moisture, temperature, altitude and soil pH. Moreover, this study underlines the importance of certain vegetation types and geological bedrocks in determining the distribution and abundance of orchids. In total, eight ecological groups of orchids were distinguished. The results have shown that 11 orchid taxa are indicators of specific vegetation types, whereas 13 orchid taxa are indicators of specific bedrock types. The study area provides suitable conditions for survival of some rare and endemic orchid species that have southern limits of their distribution in this part of southeastern Europe. The study suggests that the joint effect of ecological factors, especially vegetation communities and bedrock types, is important to consider in the planning and management of orchid species conservation.